2008
DOI: 10.1002/chir.20660
|View full text |Cite
|
Sign up to set email alerts
|

Racemic compound against racemic conglomerate formation: The crystal properties of allylbenzylmethylphenylphosphonium iodide as compared with the nitrogen analogue

Abstract: Although racemic allylbenzylmethylphenylammonium iodide 1b displays spontaneous resolution crystallizing in a homochiral mode as a conglomerate, its phosphonium analogue rac-2b crystallizes in a heterochiral lattice forming racemic compound in the solid state. The more pronounced conformation freedom for 2b molecules manifests itself by multiple molecules crystallization (Z' = 3) of (S)-2b with the three independent molecules having different conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The phenomenon of Z′ > 1 crystal structure formation has been extensively studied for the last few years. [1][2][3][4][5][6][7][8] The origins of this phenomenon are still largely unclear, though various reasons have been put forward to explain them. Thus, Desiraju 2 has recently suggested that some high Z′ structures may be metastable relics of fast growing crystal nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of Z′ > 1 crystal structure formation has been extensively studied for the last few years. [1][2][3][4][5][6][7][8] The origins of this phenomenon are still largely unclear, though various reasons have been put forward to explain them. Thus, Desiraju 2 has recently suggested that some high Z′ structures may be metastable relics of fast growing crystal nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…They are thus of interest whenever processes implementing such compounds and transformations are pursued. They also suggest further exploration, for instance, towards exchanges and DCLs based on other nucleophilic substitution reactions (e.g., R−X/R′−Y) or towards other classes of compounds such as quaternary phosphonium salts, or also towards other types of applications such as the generation of dynamic ionic liquid phases, thus pushing further the realm of dynamic structural diversity and functional complexity.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the phenomenon of compound crystallization with more than one independent molecule has been extensively studied. [1][2][3][4][5][6][7][8] Among chiral compounds, this phenomenon occurs more commonly than among racemic ones. This fact is obviously caused by a limited set of symmetry elements in chiral space groups and, accordingly, with a hindrance to the realization of one or another homochiral associate in a crystal.…”
Section: Introductionmentioning
confidence: 99%